2015
DOI: 10.1055/s-0034-1398491
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatility Index in Carotid Arteries is Increased in Levothyroxine-Treated Hashimoto Disease

Abstract: The aim of this case-control study was to evaluate carotid hemodynamic variables and traditional cardiovascular risk factors in women with Hashimoto thyroiditis (HT). The study group consisted of 31 females with HT on levothyroxine (L-T4) and 26 euthyroid women with HT without L-T4 matched for age and body mass index (BMI) as controls. Carotid intima-media thickness (CIMT), carotid extra-media thickness (CEMT), and pulsatility indexes in common carotid artery (PI CCA) and in internal carotid artery (PI ICA) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Timing and magnitude of reflected waves was determined by hypothyroidism and improved after replacement therapy, indicating a positive effect on arterial stiffness [ 40 ]. Other studies focused on biomarkers of structural arterial stiffening, as β index [ 25 , 42 , 43 ], pulsatility index in carotid arteries [ 44 ] or brachial-ankle PWV [ 21 ]. One large study conducted in a large population, with brachial-ankle PWV, did not find a significant difference between hypothyroid and euthyroid subjects, which adds heterogeneity in the results [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Timing and magnitude of reflected waves was determined by hypothyroidism and improved after replacement therapy, indicating a positive effect on arterial stiffness [ 40 ]. Other studies focused on biomarkers of structural arterial stiffening, as β index [ 25 , 42 , 43 ], pulsatility index in carotid arteries [ 44 ] or brachial-ankle PWV [ 21 ]. One large study conducted in a large population, with brachial-ankle PWV, did not find a significant difference between hypothyroid and euthyroid subjects, which adds heterogeneity in the results [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…One large study conducted in a large population, with brachial-ankle PWV, did not find a significant difference between hypothyroid and euthyroid subjects, which adds heterogeneity in the results [ 45 ]. More recently, studies that evaluated the gold-standard measure of aortic stiffness, the carotid-femoral PWV [ 33 , 44 ] or the heart-femoral PWV [ 35 ], found an increase in arterial stiffness markers in patients with overt hypothyroidism.…”
Section: Resultsmentioning
confidence: 99%
“…PI CCA and PI ICA were both increased in the study group when compared to the controls (p = 0.02 and p = 0.047), while CIMT and CEMT were similar in both groups. The authors concluded, that it was the hormonal imbalance of hypothyroidism that influences arterial stiffness, and not the autoimmune disease process itself, that causes arterial stiffness [48]. In a more recent study by Kalantari [49], he investigated the use of color doppler and gray scale ultrasound on predicting thyroid nodule malignancy.…”
Section: Pulsatility Index and Thyroid Diseasementioning
confidence: 99%
“…Thus, both hypo- and hyperthyroidism significantly alter these processes, resulting in significant changes in body composition ( 7 , 8 ). Moreover, many thyroid disorders are associated with chronic inflammation, with the latter altering systemic response independently of thyroid hormones ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%